2018
DOI: 10.1021/acsami.8b08153
|View full text |Cite
|
Sign up to set email alerts
|

Absorbent Filaments from Cellulose Nanofibril Hydrogels through Continuous Coaxial Wet Spinning

Abstract: A continuous and scalable method for the wet spinning of cellulose nanofibrils (CNFs) is introduced in a core/shell configuration. Control on the interfacial interactions was possible by the choice of the shell material and coagulant, as demonstrated here with guar gum (GG) and cellulose acetate (CA). Upon coagulation in acetone, ethanol, or water, GG and CA formed supporting polymer shells that interacted to different degrees with the CNF core. Coagulation rate was shown to markedly influence the CNF orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 42 publications
1
55
1
Order By: Relevance
“…With optimized parameters, fibres have been manufactured with high stiffness (86 GPa) and tensile stress (1.57 GPa) (Mittal et al 2018); these values are much higher compared to the properties of known natural or synthetic biopolymeric materials. Finally, functional systems, e.g., magnetic (Walther et al 2011), superabsorbent (Lundahl et al 2018b), electroconductive (Wan et al 2019;Chen et al 2020), water-resistant (Cunha et al 2018Tripathi et al 2018), bioactive (Vuoriluoto et al 2017) fibres can be obtained by modification of the spinning dope, coagulants, and subsequent post-treatment.…”
Section: Tocnfmentioning
confidence: 99%
“…With optimized parameters, fibres have been manufactured with high stiffness (86 GPa) and tensile stress (1.57 GPa) (Mittal et al 2018); these values are much higher compared to the properties of known natural or synthetic biopolymeric materials. Finally, functional systems, e.g., magnetic (Walther et al 2011), superabsorbent (Lundahl et al 2018b), electroconductive (Wan et al 2019;Chen et al 2020), water-resistant (Cunha et al 2018Tripathi et al 2018), bioactive (Vuoriluoto et al 2017) fibres can be obtained by modification of the spinning dope, coagulants, and subsequent post-treatment.…”
Section: Tocnfmentioning
confidence: 99%
“…In the course of our work on CNF spinning, it was found that the use of a carrier polymer, in a coaxial configuration, made possible the formation of continuous filaments [34]. We found that cellulose acetate (CA) and guar gum (GG) were effective for this purpose, while allowing control of filament properties by their inherent differences in hydrophilicity and solvency.…”
Section: Introductionmentioning
confidence: 99%
“…Foams prepared from neat CNF exhibited a water absorption capacity of 19 g/g (for the two crosslinker loading levels). The strong affinity of CNF towards water is a result of the abundance of hydroxyl groups 36 .…”
Section: Resultsmentioning
confidence: 99%